Aequidens superomaculatum (Teleostei: Cichlidae) una nueva especie del alto Orinoco y Río Negro, Venezuela (2015)
A new species, Aequidens superomaculatum, is described from the Casiquiare Canal drainage and the upper reaches of the Orinoco and Negro rivers (Venezuela). This new species shares with others of the genus a vermiculated color pattern on the cheek, snout and preopercle and a high vertebral count, but it differs from congeners in having a continuous lateral stripe, and in having the lateral dark pigment blotch positioned high on both sides of the body.